Bupropion Sustained released versus Placebo for seasonal affective Disorder - Martin H Teicher; Danielle M Webster; Steven B Lowen (Archives of Depression and Anxiety - Peertechz Publications, 2017)
Background: The majority of seasonal affective disorder  (SAD) studies have evaluated  the  use of   light or selective serotonin reuptake inhibitors (SSRI). The purpose of the present study was to evaluate bupropion sustained-released (SR), a non-SSRI antidepressant, for the treatment of SAD. Method:  Forty-one adults meeting DSM IV criteria for SAD were recruited into a six-week, randomized, double-blind,  placebo-controlled trial. Participants started on bupropion  SR  150  mg  QD  (or  equivalent placebo  pills)  and  titrated  up  to  200  mg BID  if  tolerated  by  week 4. Participants  were  evaluated weekly with SIGH-SAD and self-reported Kellner Symptom Questionnaire (SQ). Mixed effects growth models and receiver operating characteristic (ROC) analyses were used to compare treatments. Results : Analysis was done on the 36 participants who completed at least 2 weeks of treatment, as per protocol. Thirty-four participants  completed the entire  protocol; two  participants receiving placebo dropped  out  during  weeks 3 and 5. Sixteen  participants  (7 male, 9 female, 46.5  +  9.6  years, mean+SD) received bupropion SR and 20 participants  (8 males, 12 females,  48.2+8.8  years)  received  placebo.  Participants  receiving  bupropion  SR had a more rapid reduction  in  atypical  SIGH-SAD  depressive  symptoms and lower depression scores across time on the SQ. ROC  analyses  revealed  that  positive effects of bupropion SR on total SIGH-SAD scores were more evident in males than females. Bupropion SR was well tolerated. Conclusion : Bupropion SR may be beneficial for the treatment of SAD, but larger randomized placebo- controlled studies are warranted